A Relationship between Uterine Cervical Cytopathology and Histopathology in Mongolia (Central Asian Journal of Medical Sciences, 2020)
Objectives: This study aimed to evaluate the correlation between uterine cervical squamous cell abnormalities by conventional cytology and corresponding histopathology, and to assess the accuracy between them. Methods: A total of 192 cytological smears of patients with squamous cell abnormalities who underwent colposcopy examination from April – December 2015 were included in this study. The final agreement between cytology and histopathology was defined by the evaluation of histology as a golden standard. Results: The agreement between cytology and histopathology evaluation was 65.6%, and the discrepancy was 33.6% (k=0.512). When the classes of cytology were evaluated for accuracy, it was discovered that NILM* had a higher sensitivity of 77.0%, a specificity of 87.0%, a false positive of 23% and a false negative of 13.0% (k=0.711). Among the LSIL cases a sensitivity was discovered of 39.0%, a specificity of 82.7%, a false positive of 61.0% and a false negative of 17.3% (k=0.392. However, in HSIL sensitivity dropped to 37.8%, specificity increased to 91.6%, false positive were 62.0% and false negative were 8.4% (k=0.501). Conclusion: The agreement for diagnosis of uterine cervical cytology and histopathology was 65.6% (n = 126) and the discrepancy was 33.6% (n = 64) (p = 0.001). The correlation between cervical cytology and histopathology remained moderate (kappa=0.512). Thus, it is proposed that an appropriate quality control system for the cytopathological confirmation may contribute to the further detection and treatment for uterine cervical cancer in Mongolia.